Measurements and characterization of power transformer and low voltage access network for NB‐PLC. (28th June 2017) - Masood, Bilal; Usman, Muhammad; Gul, Muhammad Usman; Khan, Waheed Aftab
Summary: Several techniques for a state‐of‐the‐art advanced metering infrastructure (AMI) within the smart grid are being extensively studied and evaluated around the world. Advanced metering infrastructure provides an enhanced and efficient energy management infrastructure that can facilitate the latest demands of electric utilities, consumers, and smart grid. In the past few years, standardization process for the implementation of AMI using narrowband power line communications (NB‐PLC) transceivers has been completed by ITU‐T and IEEE. This paper is focused on the utilization of CENELEC band of NB‐PLC for deployment aspects. The power transformer model of 200 and 75 kVA transformers for 9 to 90 kHz frequency range that lies in CENELEC‐A band of NB‐PLC is also proposed. The proposed model is more simple than previously presented models in the literature and has the capability to evaluate the transformers working not only under normal condition but also under resonance condition for frequency of interest. Moreover, the efficient procedure for field measurements that provides a generalized NB‐PLC channel model for low voltage access network to deploy AMI within Lahore, Pakistan, is presented. A Simulink model is developed to validate the results. The analysis of measured and simulated results illustrates a close agreement of channel transfer functions. This research work proposes an improved and more accurate NB‐PLC channel model especially for South Asian countries. Abstract : The novelty of the proposed model in this paper is that it can be a useful simulation model that can develop understanding for the educational purposes by studying and simulating the behavior of transformers in the frequency of interest. Another novel aspect of this research work lies in the fact that various channels of Lahore City that encompass all possible types of power line channels have been evaluated from both field measurements and Simulink model.